The Effectiveness of Cinema Therapy in Reducing Bullying Behavior in Islamic Boarding Schools - Derry Okpriansyah; Suryati Suryati; Hartika Utami Fitri (Scidacplus, 2025)
Bullying remains a significant psychosocial problem in Islamic boarding schools, potentially affecting students' psychological well-being, social relationships, and academic development. This study aimed to examine the effectiveness of Cinema Therapy in reducing bullying behavior among students at Ar-Risalah Modern Islamic Boarding School, Lubuklinggau, Indonesia. A quantitative pre-experimental design with a one-group pretest–posttest approach was employed. The study involved eight students selected through probability sampling techniques. Data were collected using a bullying behavior questionnaire and observational measures. Instrument validity and reliability were assessed prior to data analysis. The collected data were analyzed using the Wilcoxon Signed-Rank Test with the assistance of SPSS version 22. The findings indicated that the participants initially exhibited a high level of bullying behavior. Following the implementation of the Cinema Therapy intervention, bullying behavior scores decreased significantly. Statistical analysis revealed a significant difference between pretest and posttest scores (Asymp. Sig. = 0.012, p < 0.05), indicating that the intervention had a positive effect on reducing bullying behavior. These findings suggest that Cinema Therapy is an effective counseling intervention for decreasing bullying behavior among students in Islamic boarding school settings. The study contributes to the development of innovative counseling strategies aimed at fostering a safer and more supportive educational environment.